1998 International Conference on Power Electronic Drives and Energy Systems for Industrial Growth, 1998. Proceedings.
DOI: 10.1109/pedes.1998.1329995
|View full text |Cite
|
Sign up to set email alerts
|

An improved three-level shunt active filter

Abstract: Abstract:A shunt active filter is capable of removing harmonic currents from the supply of commercial and industrial sites. This paper presents a novel method for generating the compensating current signal for an active filter that uses a three-level inverter to provide a fast transient response. It is shown that the active filter must be positioned downstream of the power factor correction capacitors for stable operation. A new compensating current technique, based on sinusoidal subtraction, together with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…A shunt active filter is capable of removing harmonics from the supply of commercial and industrial sites. Simon Round and friends use the new technique based on sinusoidal subtraction by using active filter to make an inverter which is more responsive to the harmonics [4].…”
Section: Active Filtermentioning
confidence: 99%
“…A shunt active filter is capable of removing harmonics from the supply of commercial and industrial sites. Simon Round and friends use the new technique based on sinusoidal subtraction by using active filter to make an inverter which is more responsive to the harmonics [4].…”
Section: Active Filtermentioning
confidence: 99%
“…Various solutions are reported in the literature for addressing the aforementioned instability problem [14, 16–32]. In [16–22], it has been reported that the instability problem can be avoided by repositioning the PFC capacitors at a point which is upstream to the point of sensing of the load current. By employing this scheme it is ensured that the current drawn by the PFC capacitors does not get included in the feedback path of the harmonic compensation loop.…”
Section: Introductionmentioning
confidence: 99%
“…The above two classification criteria broadly divide the current control strategies into following four harmonic compensation schemes: (a) THC with direct current control [34]. (b) THC with indirect current control [25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in the literature that irrespective of the type of the current control scheme being employed for an AHF, the presence of PFC capacitors affects the operational behaviour of the AHF [34–58]. The operation of AHF can become unstable while compensating certain higher‐order harmonic components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation